Intensive, Regular Sampling and Removal of Modest Numbers of Fishes Shows No Measurable Impact on Fish Populations in Three Streams of North Georgia - Steven L Powers (Southeastern Fishes Council Proceedings, 2016)
Recent publications and restrictions on collecting by state fish and game managers indicate a growing concern regarding the impact of field sampling on native fish populations. To evaluate the validity of these concerns, data from five life-history studies conducted in Cherokee County, Georgia were examined to test the hypothesis that regular sampling has a negative impact on fish populations. Number of individuals collected was divided by time collecting to calculate catch per unit effort (CPUE) as an indicator of relative abundance for each species. The collecting sequence (i.e. the number of times a species had previously been sampled) was regressed against CPUE for each of the five species. Despite monthly electrofishing and removing up to hundreds of individuals of each species, there was no significant relationship between CPUE and the collecting sequence (r2 = 0.1%, P = 0.82). Only one species, the imperiled Etheostoma scotti, Cherokee Darter, showed a negative correlation (-0.1) between CPUE and collecting sequence, but the association was weak (r2= 0.1%) and not significant (P = 0.76). These data suggest that even intensive, regular sampling and removal of modest numbers of individuals from the same reach of a small stream (< 10 m wide) had no measurable long-term impact on stream fish populations. Therefore, concerns regarding of the impact of collectors on stream fish populations may not be consistent with the actual impact of collectors.
Keywords: electroshocking; endangered species; Etheostoma scotti